MUZAKKI SEBAGAI INVESTOR DALAM PENGELOLAAN ZAKAT PRODUKTIF (PENGEMBANGAN EKONOMI UMMAT MELALUI SISTEM ZAKAT PRODUKTIF BAZNAS) - Nur Azizah (Al-'Aqdu: Journal of Islamic Economics Law, 2021)
This era of globalization is full of challenges of the times, including the nation's economic problems. The majority of Indonesian people are Muslims, where there is an obligatory ibadah to give zakat if the assets have reached the haul and nisab. In Indonesia, there is an Amil Zakat Agency called BAZNAS. The zakat regulation in Indonesia is Law NO. 23 of 2011 concerning zakat management, guidance on the implementation of productive zakat. Productive zakat is learning zakat funds to generate profit (profit). Of course, this is a very profitable and effective zakat system if implemented effectively and efficiently. However, the problem is the lack of zakat funds to measure large-scale business development. The solution that is used following the times is an investment model. Where muzakki are used for their capital services, if the investment returns of the investors reach the haul and nisab, their zakat can be withdrawn. It is profitable to pay the muzakki tax fee.Keywords: Investment; Muzakki; Productive Zakat.AbstrakDi masa globalisasi ini penuh dengan tantangan zaman, termasuk masalah ekonomi bangsa. Mayoritas masyarakt Indonesia adalah beragama Islam, di mana terdapat suatu ibdah wajib untuk berzakat jika harta telah mencapai haul dan nishab. Di Indonesia sendiri terdapat Badan Amil Zakat yang disebut BAZNAS. Peraturan zakat di Indonesia yakni UU NO. 23 Tahun 2011 tentang pengelolaan zakat mengatur tentang pelaksanaan zakat produktif. Zakat produktif adalah pengumpulan dana zakat untuk kemudian dikelola supaya menghasilkan laba (untung). Tentunya ini adalah system zakat yang sangat menguntungkan dan efektif jika terlaksana secara efektif dan efisien. Tetapi permasalahan yang timbul adalah kurangnya dana zakat untuk kukuran pengembangan usaha skala besar. Solusi yang dipakai mengikuti zaman adalah model investasi. Di mana muzakki digunakan jasa modalnya. Apabila laba investasi para investor mencapai haul dan nishab maka dapat ditarik zakatnya. Hal ini menguntungkan terlebih terdapat aturan pengurangan biaya pajak bagi muzakki.Kata kunci: Investasi; Muzakki; Zakat Produktif.